Mind Web In Teaching Writing Skills at English Language Education Study Program of IAIN Palopo - Tri Endar Yogi (FOSTER: Journal of English Language Teaching, 2020)
The aim of this study is to find out the effective way to apply Mind Web effectively in teaching writing skill at the fifth semester students of English Language Education Study Program of IAIN Palopo. This study used Classroom Action Research. The target populations of this research were all of the fifth semester students at IAIN Palopo. The sample was taken from population by using Purposive Sampling technique. This case the research took 15 students of class B as a sample. The procedure of the research used three cycles namely cycle 1, cycle 2, and cycle 3 to find out the ability of the students in writing skill. Before explaining the material, the researcher motivated the students. For instance, the researcher told the students to study hard because their parents spent more money for their education, so they must study hard so that they could improve their skill in English especially in writing skill. The final result found that the effective ways to teach writing skill to students using mind web were: (1) Dividing the students into groups. So, the researcher could control the class easily; (2) Telling the students to make a good composition in a few minutes. The researcher also went around to each group to observe activities of students whether they write a good or not good in writing composition; and (3) Closing the meeting by suggesting them to study hard and consult the difficulties they found to their teachers. This situation of the teaching and learning process became more enjoyable, interesting and effective.